A critical analysis of the doctrine of common purpose: special reference to South Africa, Zimbabwe, England and New South Wales - Munangati, Nyaradzo Priscilla (Centre for Law and Society, 2025)
The aim of this paper is to examine the application of the doctrine of common purpose. The jurisdictions of South Africa, Zimbabwe, England and New South Wales have been chosen as points of reference, as the doctrine is still used by the prosecution in these jurisdictions in handling criminal matters where there is more than one defendant or accused person participating in the same unlawful enterprise. Most interesting is the fact that, these jurisdictions often refer to and rely on the decisions of each other, and sometimes even adopt the laws of the other jurisdiction to form part of the domestic law. This is apparent between South Africa and Zimbabwe; Zimbabwe and England; and England and New South Wales. Zimbabwe has shown a tendency to rely on South African law on common purpose as South Africa has managed to refine its laws on common purpose over the years. While South Africa would not hesitate to refer to Zimbabwean decisions as persuasive authority especially on the issue of dissociation, it is reluctant to refer directly to English law on dissociation. The irony however lies in the fact that, the Zimbabwean law on dissociation was in fact adopted from England without any changes at all and is in fact English law in all respects. This will become clear as one reads through this work. New South Wales law on. both common purpose and dissociation has been greatly influenced by English law, in fact, the law on dissociation is purely English law which was adopted. However, New South Wales stands out above the rest of the jurisdictions in so far as it distinguishes between "foundational crime" and "incidental crime" when dealing with offences perpetrated by parties to a common purpose. The whole legal scenario makes the examination of the application of the common purpose doctrine in the four jurisdictions not only interesting but exciting as well. It will be noted that in South Africa legal scholars have shown considerable zeal and interest in examining and dealing with issues pertaining to the application of the doctrine. Quite a number of articles by South African scholars are referred. to in this paper. Some of the articles were prompted by court decisions made in matters involving political unrest during the apartheid era, while others were written purely as a matter of scholarly academic interest. Unfortunately for Zimbabwe there are very, very few articles on the issue, and hence for the purpose of this paper there was heavy reliance on case law. As regards England and New South Wales, fairly recently published books were of invaluable assistance as they gave the most up to date information on how the doctrine of common purpose operates in England and in New South Wales. Case law was also heavily relied on. The paper not only relates how the doctrine has been perceived in each of the three jurisdictions but, there was also an attempt to display how the doctrine works, how issues of conduct and the mental element are dealt with,and finally any concerns which either the courts, the legal scholars or the writer find themselves confronted with.